The Evolving Marketing Mix in the Digital Age and Customer Mix: How Does It Affect Purchase Intention? - Pitri, Tedi; Firmansyah, Irman; Rijanto, Raden; Firmansyah, Deri (IJBLE Scientific Publications Community Inc., 2025)
The era of technological disruption in the 21st century is increasingly challenging the traditional 4P marketing mix concept to evolve to facilitate the creation of hybrid communication and services in the digital environment. This study aims to explore the causality predictive model between the evolution of the 4P marketing mix model and the customer mix considered in the modern business landscape of the digital age, by analyzing how it affects the purchase intention?, the mediating effect of the customer mix is examined. Quantitative research with a survey type is developed in predictive causality modeling, relying on the power of prediction. The statistical analysis applied Partial Least Squares-Structural Equation Modelling 4 (PLS-SEM4). The survey was conducted to 89 selected respondents with a purposive sampling technique approach. The findings of the study show that the evolution of the 4P marketing mix positively and significantly has a direct and indirect effect on purchase intention. The customer mix has a positive and significant effect on purchase intention. The customer mix has a positive mediating effect with moderate predictive power. These findings can fill the gap and expand the recognition that the evolution of the 4P marketing mix that is aligned with technological developments has relevance to the modern business landscape based on digital platforms. The evolution of the 4P marketing mix in the digital age, which integrates the customer mix as an important mediator in customer-centric platform-based business operations, plays a major role in attracting purchase intention.